Prospective colonoscopic study to investigate risk of colorectal neoplasms in first-degree relatives of patients with non-advanced adenomas. Issue 2 (26th April 2019) - Ng, Siew C; Kyaw, Moe Htet; Suen, Bing Yee; Tse, Yee Kit; Wong, Martin C S; Hui, Aric J; Tak, Hui Yee; Lau, James Y W; Sung, Joseph J Y; Chan, Francis K L
Abstract : Objective: The risk associated with a family history of non-advanced adenoma (non-AA) is unknown. We determined the prevalence of colorectal neoplasms in subjects who have a first-degree relative (FDR) with non-AA compared with subjects who do not have an FDR with adenomas. Design: In a blinded, cross-sectional study, consecutive subjects with newly diagnosed non-AA were identified from our colonoscopy database. 414 FDRs of subjects with non-AA (known as exposed FDRs; mean age 55.0±8.1 years) and 414 age and sex-matched FDRs of subjects with normal findings from colonoscopy (known as unexposed FDRs; mean age 55.2±7.8 years) underwent a colonoscopy from November 2015 to June 2018. One FDR per family was recruited. FDRs with a family history of colorectal cancer were excluded. The primary outcome was prevalence of advanced adenoma (AA). Secondary outcomes included prevalence of all adenomas and cancer. Results: The prevalence of AA was 3.9% in exposed FDRs and 2.4% in unexposed FDRs (matched OR (mOR)=1.67; 95% CI 0.72 to 3.91; p=0.238 adjusted for proband sex and proband age). Exposed FDRs had a higher prevalence of any adenomas (29.2% vs 18.6%; mOR=1.87; 95% CI 1.32 to 2.66; p<0.001) and non-AA (25.4% vs 16.2%; mOR=1.91; 95% CI 1.32 to 2.76; p=0.001). A higher proportion of exposed FDRs than unexposed FDRs (4.3% vs 2.2%; adjusted mOR=2.44; 95% CI 1.01 to 5.86; p=0.047) had multiple adenomas. No cancer was detected in both groups. Conclusion: A positive family history of non-AA does not significantly increase the risk of clinically important colorectal neoplasia. The data support current guidelines which do not advocate earlier screening in individuals with a family history of non-AA. Trial registration number: NCT0252172 .